Influencing Factors of Patient Safety Culture: A Quantitative Study - Makiah, Makiah; Noermijati, Noermijati; Hadiwidjojo, Djumilah; Moko, Wahdiyat (AIBPM Publisher, 2023)
Patient safety culture is an important aspect in healthcare organizations. This study aims to determine the factors that influence the implementation of patient safety culture in a regional public hospital on Lombok Island. This study is a quantitative study with an analytic survey using a cross-sectional design. The sample in this study was 127 inpatient room nurses using proportionate random sampling technique. Data collection was carried out by distributing questionnaires, then analyzing the data using multiple linear regression with the research findings of leadership effectiveness, work motivation and knowledge management have a significant effect on the implementation of patient safety culture. That the leadership effectiveness variable is the dominant variable influencing the implementation of patient safety culture in regional public hospitals on Lombok Island.